Strain, loss of time, or even gain? A systematic review of technology-based work extending and its ambiguous impact on wellbeing, considering its frequency and duration - Schoellbauer, Julia; Hartner-Tiefenthaler, Martina; Kelliher, Clare (Frontiers in Psychology, 2023)
Especially in knowledge-intensive professions, workers engage in work-related communication and access digital work content outside of working hours. Scientific research on technology-based work extending has flourished in recent decades, but yielded inconclusive results about its relationship with workers' wellbeing and focused on different temporal characteristics of the behavior. Consequently, in this article, we address the question of whether different temporal characteristics of technology-based work extending, such as the frequency and duration of the behaviour, may have different consequences for workers’ wellbeing. In the course of a systematic literature review, we analysed 78 empirical studies published between 2007 and 2021 that investigate the relationship between the self-rated frequency and the self-rated duration of work extending behaviours and 14 wellbeing indicators. Whereas most studies examined the frequency of work extending behaviours and its consequences, only 19 studies examinded the effects of its duration. Based on our findings, we propose three effects: The strain effect of frequent work extending, the gain effect of sustained work extending, and the loss-of-private-time effect inherent to work extending and independent from its frequency and duration. Our findings not only provide in-depth information on a widespread contemporary behaviour and its psychological implications, we also reveal research gaps and shed light on behaviours associated with role transitions and thus contribute to boundary theory.